The Role of Lead and Cadmium in Gynecological Malignancies - Gabriela Furtak; Mateusz Kozłowski; Sebastian Kwiatkowski; Aneta Cymbaluk-Płoska (MDPI AG, 2022)
Lead and cadmium are non-essential and toxic heavy metals. Their presence and elevated levels can lead to many pathologies. They disrupt the antioxidant properties of many enzymes, consume the resources of antioxidant cells, and thus participate in the generation of oxidative stress, which may result in DNA damage. In addition, they have been found to be carcinogenic through their genotoxic properties. They have been shown to be present in various types of cancer, including cancer of the female reproductive system. Both metals have been recognized as metalloestrogens, which are important in hormone-related cancers. Participation in the oncogenesis of ovarian, endometrial and cervical cancer was analysed in detail, using the available research in this field. We emphasize their role as potential biomarkers in cancer risk and diagnosis as well as advancement of gynaecological malignancies.